2016
DOI: 10.1080/07924259.2016.1244572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on the embryonic development ofMacrobrachium acanthurus(Decapoda: Palaemonidae)

Abstract: Palaemonid shrimps occur in the tropical and temperate regions of South America and the Indo-Pacific, in brack-ish/freshwater habitats, and marine coastal areas. They form a clade that recently (i.e., ~30 mya) invaded freshwater, and one included genus, Macrobrachium Bate, 1868, is especially successful in limnic habitats. Adult Macrobrachium acanthurus (Wiegmann, 1836) dwell in coastal freshwaters, have diadromous habit, and need brackish water to develop. Thus, they are widely recognized as euryhaline. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Fukuda et al. (2017), using females captured in the same region as this study and after reproduction in captivity, found a similar incubation time (approximately 12 days) at the same temperature (29°C). However, in the south of Brazil this species exhibited more prolonged development (16 days at 25°C) (Müller et al., 2007).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Fukuda et al. (2017), using females captured in the same region as this study and after reproduction in captivity, found a similar incubation time (approximately 12 days) at the same temperature (29°C). However, in the south of Brazil this species exhibited more prolonged development (16 days at 25°C) (Müller et al., 2007).…”
Section: Discussionsupporting
confidence: 68%
“…This statistical difference is biologically insignificant (since smaller than one day) and hence does not have implications for the farming of the species. Fukuda et al (2017), using females captured in the same region as this study and after reproduction in captivity, found a similar incubation time (approximately 12 days) at the same temperature (29°C). However, in the south of Brazil this species exhibited more prolonged development (16 days at 25°C) (Müller et al, 2007).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Egg volume increased significantly during egg (Nazari et al, 2003;Zhao et al, 2007). The volume increase in the developing egg may be due to water osmotic uptake (Fukuda et al, 2016). Changes in the egg size throughout the development is important as osmotic swelling facilitates the outer membrane rupture for hatching process (Soundarapandian, 2008).…”
Section: Post Nauplius Stagementioning
confidence: 99%